Pelatihan Strategi Business Model Canvas (BMC) pada Usaha Brem UD. Duta Rasa Madiun - Daroin, Ana Dhaoud; Andriani, Dwi Nila; Sari, Novita Erliana; Putra, Kevin Prasetya Aditya; Wardana, Alfarin Yogi (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The community service activities of the PGRI Madiun University team aim to (1) Educate business actors about the urgency of business development with the Business Model Canvas (BMC) strategy, (2) Establish company effectiveness through the implementation of the business model canvas. This community service activity uses the ABCD method. The service team empowers existing assets in UD. Duta Rasa and improve business management with BMC to create a good corporation. This activity was initiated by holding a business model canvas training as the implementation of a good corporation. The outputs of this research are articles, business model canvas (BMC) strategy flow, activity videos, and intellectual property rights/patents in the form of a Business Model Canvas (BMC) development manual at UD. Taste Ambassador. Based on interviews and observations conducted with the parties involved, business actors, and communities who were the target of the training, there was enthusiasm and enthusiasm for the target participants and the benefits of the training program.